A New Copyright Protection for Vector Map using FFT-based Watermarking - Shelvie Nidya Neyman; I Nyoman Prama Pradnyana; Benhard Sitohang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
This study proposed a new approach of copyright protection for vector map using robust watermarking on FFT algorithm. A copyright marker inserted in vector map as the watermark. In addition to data origin authentication capabilities watermark, RSA cryptographic algorithm is used when generating the watermark. Quality measurement of the results was based on the three characteristics of digital watermarking: (1) invisibility using RMSE calculations, (2) fidelity with the farthest distance and (3) NC calculation and gemotrical level of robustness against attacks. Result of experiments showed that the approach used in this study succeeded in inserting copyright as watermark on vector maps. Invisibility test showed good results, demonstrated by RMSE close to zero. Fidelity of the watermarked map was also maintained. Level of watermark robustness against geometric attacks on vector map results has been maintained within the limits that these attacks do not affect the watermark bit value directly.